Helping under a Combination of Team and Tournament Incentives - Anastasia Danilov; Bernd Irlenbusch; Christine Harbring (Institute of Labor Economics (IZA), 2019)
We study how help can be fostered by means of a team bonus in the presence of rank-order tournaments. In a simple model we combine elements of relative rewards and a team bonus and study their effect on effort, help and sabotage. Quite intuitively the theoretical analysis suggests that team members help less as relative rewards increase. This problem is mitigated by a team bonus that is proportional to the output of the whole team. We compare different parameter constellations of the theoretical benchmark with behavior observed in a one-shot experiment.
Keywords: M52; J33; J41; L23; C72; C91; 330; help; relative rewards; team incentives; experiment